The foreign direct investment-environment nexus: does emission disaggregation matter? - Opoku, Eric Evans Osei; Adams, Samuel; Aluko, Olufemi Adewale (2021)
This paper examines the effect of foreign direct investment (FDI) on CO2 emissions by using disaggregated emissions data; territorial-based and consumption-based emissions. FDI is measured in three ways; inflow, net inflow, and stock. Employing data over the period 1995–2014 and a number of estimators, the results indicate FDI (whether measured as inflow or net inflow) has negative impact on emissions (irrespective of the measurement). However, the impact is generally found to be greater for the territorial-based emissions. The results of the FDI flow variables largely support the pollution halo hypothesis. Thus, the results are supportive of the robust effect of FDI’s positive effect. Regarding the stock measure, the negative effect of FDI is only found for the territorial-based CO2 emissions. Since the territorial-based emissions capture emissions in the domestic economy only, it is not surprising that the plausible efficiency of FDI stock is found to reduce these emissions rather the consumption-based. FDI stock is now considered part of the local economy. The results of the paper are largely not parallel with previous studies that did not disaggregate CO2 emissions. This we believe is an indication that the measure of CO2 matters for the analyses of the FDI-emissions nexus.